Cross Reaction of Haemonchus Contortus ANTIGEN WITH ANTI-Fasciola Gigantica Serum by Using Western Blot Technique - Firman Hadi Fanani; Kusnoto Kusnoto; Poedji Hastutiek; Setiawan Koesdarto; Endang Suprihati (Universitas Airlangga, 2020)
The purpose of this research to know cross reaction of Haemonchus contortus protein with anti-Fasciola gigantica serum by using the Western Blot technique. The result can be used as Haemonchosis serologic diagnostic. This research was conducted using Haemonchus contortus worms obtained from abomasum, especially cow worms and Fasciola gigantica worms obtained from the bile duct and gall bladder. The worms were crushed and added with Phosphate Buffer Saline (PBS) to make homogenates and then centrifuged at 3500 rpm for 15 minutes. Homogenate Fasciola gigantica was immunized to mice to get anti-Fasciola gigantica serum at a dose of 200 Î¼g/mice and booster 3 times with a span of two weeks. Homogenates were carried out using the SDS-PAGE technique to analyze proteins using a brilliant blue dye. Cross reaction of Haemonchus contortus protein with anti-Fasciola gigantica serum byusing Western blot technique and obtained 3 protein bands are 94.9, 52.7, 46.7 kDa.